Wpływ metodyki myślenia sieciowego na ewolucyjne zmiany w przedsiębiorstwie - Piekarczyk, Anna (Influence of network analysis methodology on evolutional changes in an enterprise, 2006)
The article deals with network analysis methodology, which proves to be very effective in research and management of complex systems such as contemporary enterprises. According to the method, a problem should be looked at from different points of view and interaction between its elements should be studied with the help of network. Such approach to dealing with a problem affords better possibilities for research and understanding of it (both as a whole and in its parts), as well as for observation of the evolutional process of changing, learning and developing
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 374-382